Violência e ação política em Eric Weil - Branco, Judikael Castelo (2011)
For Eric Veil, the philosophy is not a view of the world, a dogmatic or relativistic knowledge, but a commitment with the reason and freedom through the attempt of understanding the human being, his speech and his action. The purpose of this work is try to understand what the terms violence and politic action means in the philosophy of Weil, and at the same time, the meaning of philosophy itself. We start using the relationship between philosophy and violence, related to the negative act of the reason and, that´s why, the main problem for the philosophical speech in its pretension of absolute understanding. One of the Veil´s characteristics is consider what represent the problem of the violence after Hegel´s perspective of an absolutely coherent speech, so that, considering the lack of the absolute speech in order to contain the reality of the violence. As a result, we have the reflection about the relationship between violence and reasonable action in the politic area, in order to think the politics through the philosophy. Weil takes the politics as consideration of the human being living in common according to his essential structures getting back a positive relationship between moral and politics, in order to raise a philosophy that is capable of understand the modern politics and consider the politic action as a fighting against the violence, referring to nature, the relationship between individual and society and the solution in the modern state, as the owner of the monopoly of the use of violence. The state appears as a condition for the conciliation between the sensible life of the individual in the concrete moral and the imposing demand through the rationality of the modern society. Finally, a reasonable life, with the possibilities of the modern society, must find a meaning in the politic life, participating of the decisions of common interest. It´s the transposition of the problems solution of the using of violence for the debating area, through the education of the politic people, social task of the philosopher, and it´s the aim of the politic action. This reflection intends to be coherent, according to its time, must recognize that history, politics, economy, and philosophy, force the philosopher to think about the common destiny of the human kind. That´s what Weil reflects about a world state, concrete category that gather the moral categories, of society and the state, and where all these politic categories are together in the purpose of understanding the reality